Examining the Mediation Role of Parental Guilt in the Relationship between Working Mothers' Smartphone Addiction and Their Children's Problematic Technology Use - Sariyildiz, Fatma Miray; Erus, Seher Merve (TURKISH GREEN CRESCENT SOC, 2025)
This study aimed to examine the mediation of parental guilt in the relationship between smartphone addic-tion in working mothers and problematic technology use among their preschool children. A total of 260 working mothers, aged between 22 and 50, with preschool children, participated in the study. The study uti-lized the Personal Information Form, Smartphone Addiction Scale Short Form, Parental Guilt Scale, and Problematic Technology Use Scale for Children. SPSS bootstrapping analysis was applied to investi-gate the mediation of parental guilt in the relationship between mothers' smartphone addiction and their preschool children's problematic technology use. The analysis revealed that parental guilt mediated the relationship between mothers' smartphone addiction and their children's problematic technology use. The findings are discussed considering existing knowledge on smartphone addiction, parental guilt, and problem-atic technology use in children. In this direction, suggestions are presented with a focus on working mothers to reduce problematic technology use among children.
Keywords: Parental guilt; preschool period; problematic technology use; smartphone addiction; working mother; TIME; Substance Abuse